Identifying Classroom Teachers’ Challenges in Teaching Bahasa Indonesia Vocabulary in Elementary School - Rizki, Sarita; Najichah, Amalia Fajriyyatin; Uminar, Ajeng Ninda; Purwanti, Elly (LinguaScopes: International Journal of Language Education, 2025)
This study identifies and analyzes the obstacles faced by elementary classroom teachers in teaching Bahasa Indonesia vocabulary. Utilizing a qualitative descriptive research design, data was gathered through semi-structured interviews and classroom observations of two experienced teachers. Thematic analysis of the collected data revealed a range of interconnected challenges. Key findings indicate that teachers struggle with insufficient pedagogical training for vocabulary instruction, limited access to engaging teaching resources, and significant time constraints within the curriculum. Furthermore, obstacles related to student motivation and the wide variation in students' prior knowledge were found to impede effective learning. The report concludes that current vocabulary instruction is often insufficient, contributing to a persistent "vocabulary gap" among students. The findings provide crucial insights for educators and policymakers, emphasizing the need for targeted professional development, improved resource allocation, and a curriculum that better supports foundational language skills.